Income Inequality and Growth: A Panel Study of Swedish Counties 1960-2000 - Ruth-Aïda Nahum (Uppsala University, Department of Economics, 2005)
This paper explores the relationship between income inequality and growth using panel data on Swedish counties from 1960-2000. Compared to standard methods of estimating this relationship yearly regional level data are used, and inequality is allowed to be endogenous. We find a significant positive impact of inequality on growth, but the magnitude of the effect decreases with the length of the growth period studied. When allowing income inequality to be endogenous, using a panel 2SLS IV estimation, we find positive effect of inequality on 1 to 5-year growth rates, when significant, whereas the effect on 10-year growth rates are not clear cut.
urn:nbn:se:uu:diva-79352
Keywords: D31; O15; O40; 330; Income inequality; regional economic growth; panel data; Regionale Einkommensverteilung; Einkommensverteilung; Regionales Wachstum; Panel; Schweden